2012
DOI: 10.1159/000332940
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal IdeS and Its Impact on Immune Response and Inflammation

Abstract: Survival of the important bacterial pathogen Streptococcus pyogenes relies on its ability to circumvent the antimicrobial actions of innate and specific immune responses and to modulate the inflammatory responses induced during the course of an infection. Inflammatory processes play key roles during streptococcal pathogenesis and streptococcal infections are accompanied by an intense inflammatory state. As an exclusively human pathogen, S. pyogenes has adapted to the various countermeasures employed by its hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 108 publications
2
21
0
Order By: Relevance
“…Pertinent to the concept of in vivo proteolysis of IgGs was the finding that a coadministration of IdeS proteinase with trastuzumab totally abolished antitumor efficacy in the BT474 mouse xenograft model. This finding verified the potent IgG cleavage activity of IdeS and the in vivo consequences of IgG functional impairment by this proteinase and potentially others with relevance to cancer (35).…”
Section: Discussionsupporting
confidence: 76%
“…Pertinent to the concept of in vivo proteolysis of IgGs was the finding that a coadministration of IdeS proteinase with trastuzumab totally abolished antitumor efficacy in the BT474 mouse xenograft model. This finding verified the potent IgG cleavage activity of IdeS and the in vivo consequences of IgG functional impairment by this proteinase and potentially others with relevance to cancer (35).…”
Section: Discussionsupporting
confidence: 76%
“…Two study groups independently identified a non-SpeB protease with efficient IgG-degrading activity and a secreted protein with homology to the α-subunit of human Mac-1 (CD11b/CD18, CR3), resulting in the IdeS/Mac-1 nomenclature [43, 44]. IdeS/Mac-1 is a 35-kDa cysteine endopeptidase with strict specificity to IgG and is present in all strains in 1 of 2 allelic variants [45]. IdeS/Mac-1 interaction with IgG results in proteolytic cleavage at a specific site present in the lower region of the heavy chain between 2 glycine residues (G236 and G237), efficiently inhibiting complement-binding and Fc recognition (Fig.…”
Section: Secreted Complement Evasins Of Gasmentioning
confidence: 99%
“…2 (B)) [44]. Hydrolysis of streptococcal IgG antibodies by IdeS/Mac-1 produces high amounts of circulating F(ab’) 2 fragments, which can rebind to the bacterial surface but cannot mediate complement activation or immune cell signaling, thus exerting a protective effect [45]. IdeS/Mac-1 also contains an Arg-Gly-Asp (RGD) motif, a sequence commonly associated with integrin binding.…”
Section: Secreted Complement Evasins Of Gasmentioning
confidence: 99%
“…2 Proteases associated with cancer, inflammation, and infectious diseases are represented in the group. 3,4 These autoantibodies also bind to single-chain peptide analogs of the IgG1 hinge possessing defined C-termini that correspond to sites generated in IgG by protease action. 2,5 Comparable autoimmune profiles were not detected against the hinge region of intact IgG 2 or to cleavage site analog peptides with the opposing free N-termini.…”
Section: Introductionmentioning
confidence: 99%